2019
DOI: 10.3390/ani9050239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ground Transportation on Adrenocortical Activity in Prepuberal Female Mice from Five Different Genetic Backgrounds

Abstract: Specific experimental protocols necessitate transportation, a potentially stressful event that could confound results. We determined adrenocortical activity by measuring fecal corticosterone metabolites (FCMs), as a stress marker, in prepuberal (three-week old) female C57BL/6J, C57BL/6NCrl, FVB/NCrl, Crl:CD1(ICR), and BALB/cAnCrl mice. On each transport day, five female cage mates per genetic background were weaned and transported in stable groups via truck from the breeding to the research facility. Fecal pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The duration of the acclimatization period that is required varies depending on species, outcome of interest and (previous) environmental factors including diet [ 40 ]. For laboratory mice, previous studies have suggested between four days and four weeks are required to stabilize to a novel environment; this is based on different physiological stress markers as well as mouse strain [ 41 , 42 ]. Interestingly, some of the batch-to-batch variation in body weight and body composition of male mice at arrival could still be detected after the acclimatization phase in animals exposed to Grain diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the acclimatization period that is required varies depending on species, outcome of interest and (previous) environmental factors including diet [ 40 ]. For laboratory mice, previous studies have suggested between four days and four weeks are required to stabilize to a novel environment; this is based on different physiological stress markers as well as mouse strain [ 41 , 42 ]. Interestingly, some of the batch-to-batch variation in body weight and body composition of male mice at arrival could still be detected after the acclimatization phase in animals exposed to Grain diet.…”
Section: Discussionmentioning
confidence: 99%
“…stabilize to a novel environment; this is based on different physiological stress markers as well as mouse strain [41,42]. Interestingly, some of the batch-to-batch variation in body weight and body composition of male mice at arrival could still be detected after the acclimatization phase in animals exposed to Grain diet.…”
Section: Plos Onementioning
confidence: 99%
“…The duration of the acclimatization priod that is required varies depending on species, outcome of interest and (previous) environmental factors including diet (40). For laboratory mice, previous studies have suggested between four days and four weeks are required to stabilize to a novel environment; this is based on different physiological stress markers as well as mouse strain (41, 42). Interestingly, some of the batch-to-batch variation in body weight and body composition of male mice at arrival could still be detected after the acclimatization phase in animals exposed to Grain diet.…”
Section: Discussionmentioning
confidence: 99%